Edukasi Komunitas Untuk Meningkatkan Kepatuhan Minum Obat Dan Kontrol Tekanan Darah Pasien Hipertensi Di Posyandu Lansia Kradenan, Bantul - Kautsari, Farah Widya; Kiki Rizki Handayani (ABDIMAS Madani, 2026)
Hypertension is a chronic condition with a high risk of cardiovascular complications and requires optimal medication adherence to prevent further adverse outcomes. However, medication adherence among patients, particularly older adults, remains low due to limited knowledge, misconceptions about therapy, and insufficient environmental support. This community service activity aimed to improve the knowledge of older adults regarding antihypertensive medication adherence through interactive education conducted at the Kradenan Elderly Posyandu, Srimulyo, Piyungan, Bantul. The activity involved 23 participants and utilized lectures, discussions, and pre-test and post-test evaluations consisting of ten questions related to treatment adherence. The results demonstrated a significant increase in participants’ knowledge across all indicators, with the highest improvements observed in understanding that medication should not be discontinued without consultation (65.12%) and the importance of health education (43.91%). Overall, the educational intervention proved effective in enhancing the elderly participants’ understanding of the importance of taking medication regularly, recognizing the risks of uncontrolled hypertension, and implementing strategies to overcome adherence barriers such as forgetting doses and irregular health check-ups. This activity provided tangible benefits in improving the behavioral readiness of older adults in adhering to antihypertensive therapy and supporting better blood pressure control. Keywords: hypertension, medication adherence, older adults, health education